Jericoacoara: o paraíso é aqui! o turismo sustentável sob a perspectiva dos stakeholders - Oliveira, Laís Vieira Castro (2024)
This thesis asserts that sustainable tourism evolves from attitudes and behaviors shaped by personal values and the tourist's lifestyle, a role that the mere imposition of a sustainable tourism fee cannot fulfill. The coordination among all stakeholders emerges as the primary driver of effective sustainability in tourism. Theoretical frameworks such as Stakeholder Theory, Rational Action Theory, and Personal Values Theory were employed to support this argument. Additionally, the Contingent Valuation Method was utilized. The overarching goal of this thesis is to investigate sustainable tourism based on tourist attitudes and behaviors and the coordination among stakeholders, particularly regarding the imposition of a sustainable tourism fee. The research context focuses on the tourist destination of Jericoacoara, which implements a Sustainable Tourism Fee. To achieve the thesis objective, three articles were developed. The first article examined the Willingness to Pay (WTP) of tourists to enjoy a more sustainable experience. It involved a survey conducted with 386 tourists. For data analysis, descriptive analysis methods, Contingent Valuation Method, and Multiple Linear Regression were employed. Based on the findings of the research, policymakers and government officials can outline strategies with a focus on sustainability. Additionally, through this research, a better understanding of tourists' preferences and predisposition regarding fee payment was achieved. The central focus of the second article in this thesis was to analyze the role of personal values and lifestyle in shaping the sustainable behavior of tourists. For this purpose, a quantitative research approach was undertaken with a sample of 118 tourists. Techniques such as descriptive analysis, confirmatory factor analysis, and structural equation modeling were used to analyze the data.The third article is a qualitative study that aimed to understand stakeholders' perception of the sustainable tourism tax. Based on the obtained results, it was observed that the understanding of the sustainability concept varies among participants in the research. Regarding the Sustainable Tourism Tax (STT), specifically concerning the purpose and application of the collected funds, a widespread gap in understanding was noted among residents, tourists, and business owners. Overall, the study enhanced comprehension of tourist behavior regarding Sustainable Tourism Fee payment and associated elements, aiding public officials in formulating effective and transparent fiscal policies. In conclusion, the results of this thesis offer valuable insights for the sustainable development of tourist destinations, emphasizing the importance of diverse understanding of sustainability, transparent communication about the STF, and the promotion of inclusive and differentiated strategies to engage various stakeholders in preserving and enhancing the tourist destination.